As relações de hospitalidade na prestação de serviços de mobilidade corporativa na expatriação em prol da competitividade: estudo de casos múltiplos com uso da teoria de stakeholders - OTTERO, Juliana Rossi (2017)
The present research deals with corporate mobility, the displacements of expatriates sent to new work destinations and the relationships with the different stakeholders who participate in this process. The overall objective was to understand the relationship among experience management of hospitality, provision of services of the expatriation process stakeholders and the competitiveness of the organizations that carry out these corporate mobility processes. It was also sought: a) to identify the stakeholders involved in the expatriation process of the organizations surveyed; b) understand the expatriation process of these organizations; c) understand how the hospitality relationship among the organization, the expatriates and their families occurs. Based on these objectives, the research responds to the following question: Why can the management of hospitality experiences in the services offered by stakeholders benefit the expatriation processes given by the host organization and its consequent competitiveness?" In order to reach the answer, three propositions were formulated: (P1) the service management that contemplates hospitality experiences are more positive when the organization assumes the role of host in the process of corporate mobility; (P2) there is a mutual support between the organization and its stakeholders in corporate mobility, which are observed before, during and after the expatriation process; (P3) the hospitality experiences provided to the expatriate and his / her family upon arrival in the new country of residence are directly related to the competitiveness of the organization receiving this professional. As methodological procedures, it is an empirical, qualitative and exploratory research, with the adoption of the multiple case study method, through semi-structured exploratory interviews with stakeholders of the expatriation process, and the snow ball sampling method. The collection of evidence was done in a bibliographical and documentary way in articles, theses, dissertations and books. Propositions P1 and P3 were confirmed and P2 were partially confirmed.